Islamic Microfinance, Self-Efficacy, and Women's Economic Resilience - Resti Wulansari , Amelia; Daryono (Journal International Economic Sharia, 2025)
Objective: This essay aims to discuss the mediating role of entrepreneurial self-efficacy and the moderating role of Sharia governance strength in the relationships between the Islamic microfinance determinants and women’s household economic resilience.Methods:  The primary data were obtained through a survey of women users of Islamic microfinance using a quantitative research design. The relationships in question were tested with the help of regression and mediation analyses employing bootstrapping.Results:  The results show that Islamic microcredit, in combination with financial literacy and socioeconomic programs, directly and indirectly improves women’s economic resilience through an intermediary mechanism of an emotional and cognitive nature. The strong Sharia governance serves as a moderating variable in these positive relationships, enhancing the impact of microcredit on self-efficacy and economic resilience.Novelty: The scholars provided an integrated framework based on the synthesis of the Resource-Based View, Social Cognitive Theory, and Institutional Theory, illuminating the operation of Islamic microfinance at the psychological and institutional level, which has been missed in the spotlight of the available studies.Research Implication: With the created basic blueprint, the policy holders and practitioners can conceptualize the holistic functioning of Islamic microfinance, aiming at the enhancement of women’s economic resilience through a combination of financial access, capability building, psychological empowerment, and institutional trust.